Effect of Biofertilizer Formulation Dosage on Zoobenthos Abundance in Peat Soil Media - Lukito, Gayon; Syafriadiman, Syafriadiman; Hasibuan, Saberina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in March-April 2018 at the Peatland of Kualu Nenas Village, Tambang, Kampar, Riau. Method of this research was experimental method Complecetly Recommend Design (CRD) using 1 factor and 5 level of treatment(P0 without biofertilizer : control, P1: 300 g/m3, P2: 450 g/m3, P3: 600 g/m3and P4:750 g/m3). The best treatment in this research for increasing abundancy of microzoobenthos was 750 g/m3(P4) and for macrozoobenthos was 600 g/m3(P3). The diversity index (H') value for macrozoobenthos was 1.60 and the dominance value (C) was 0.53. The diversity index value (H') for macrozobenthos was 1.90 and the dominance value(C) was 0.41. As for water quality which includes temperatures ranging from 23-37 oC, pH ranges from 6-7.5, DO ranges from 3.2-8.6 mg / L, nitrates range from 0.76-22.7 mg / L, phosphates range from 1.41-3.91 mg / L. Keywords: Biofertilizer, Zoobenthos, Peat Soil